ICT Usage in School Finance Management of Selected Secondary Schools in Mbarara City. - Karamuzi, Beende Richard (Kabale University, 2024)
There is no enthusiasm about incorporating ICT into core management functions, most especially in financial management, in public secondary schools in Mbarara City. Hence, this study was intended to determine the relationship between ICT Usage and financial management practices in a sample of public secondary schools in Mbarara City. The specific objectives of the study were: i) To assess the ICT usage in selected public secondary schools in Mbarara City; ii) To examine finance management practices in selected public secondary schools in Mbarara City; iii) To establish the relationship between ICT usage and financial management in selected public secondary schools in Mbarara City. In the methodology, the study adopted a quantitative and qualitative approach using a cross-sectional research design, and data was collected from a sample of 108 respondents. The findings established that there was little ICT usage available and in use; there were great issues with the finance management practices regarding the assessment of risks involved in the management of finances and the keeping of records of all expenditures in school. Results showed that a high positive linear correlation was observed at r= +0.735 between ICT Usage and finance management practices among public secondary schools in Mbarara City. The result showed that internet, projector, interactive whiteboard, E-library, computers (with printers), and peripherals: scanners, webcams, digital cameras, and LAN had a significant and positive impact on school finance management practices (B = 1.618, t = 7.868, P < 0.000). For this reason, the null hypothesis was rejected based on the evidence that the p-value was smaller than the significance level, and an alternative hypothesis was supported that there was a significant relationship between ICT Usage and finance management practices in selected public secondary schools in Mbarara City. The study showed that there is a need for ICT Usage in schools and to increase its utilization when installed to boost ICT skills, knowledge, and competence, most especially in school finance management practices. The study recommends that assessment of risks and proper school monthly expenditure should be prioritized through the use of ICT in keeping records which in turn can improve the accuracy and accountability of school funds.